Penyarian Konstituen Organik Daging Buah Gaharu (Aquilaria malaccensis Lamk.) dengan Metode Maserasi Berbantu Microwave dan Uji Aktivitas Sebagai Antioksidan: Organic Constituent Extraction of Gaharu Fruit (Aquilaria malaccensis Lamk.) Using Microwave Assisted Maseration Method and Activity Test as Antioxidant - Imran; Nurlian; L.A. Kadir; La Agusu; Ruslan (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
This study was conducted to determine the organic constituents and to test the antioxidant activity and toxicity of gaharu fruit pulp extract (Aquilaria malaccensis Lamk.). Gaharu fruit pulp extract was obtained through Microwave Assisted Extraction (MAE) method and then extracted with a solvent with different polarity, namely ethyl acetate and n-hexane. The obtained yield of ethyl acetate extract of the gaharu fruit pulp was 40.827% w/v, whereas 0% w/v in n-hexane extract, therefore, no further test for n-hexane extract, so that the n-hexane extract was not tested for the next stage. The results of the organic constituents of the ethyl acetate extract of gaharu fruit pulp showed flavonoids, saponins, glycosides, phenols and tannins. Antioxidant activity testing was carried out using the DPPH method with vitamin C as a positive control. The results of the antioxidant activity test showed that IC50 of ethyl acetate extract of gaharu fruit pulp and vitamin C were 143.789ppm and 13.797ppm, respectively. Extracts from microwave-assisted maceration that were partitioned with ethyl acetate solvent were categorized into moderate antioxidants because the IC50 value was between 101-150ppm, while vitamin C was categorized as a strong antioxidant because the IC50 value was between 0-100ppm. Toxicity testing was also carried out on ethyl acetate extract of gaharu fruit pulp using the BSLT method. The results of the toxicity test of the ethyl acetate extract of gaharu fruit pulp showed activity with an LC50 value of 11.282ppm. Based on this research, the ethyl acetate extract of gaharu fruit pulp is considered to have an anticancer potential.